2011
DOI: 10.1111/j.1365-2672.2011.04979.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Mycobacterium avium ssp. paratuberculosis in yoghurt and in commercial fermented milk products containing probiotic cultures

Abstract: Aims:  To assess the survival of Mycobacterium avium ssp. paratuberculosis (MAP) in yoghurt and commercial fermented milk products containing probiotic strains. Methods and Results:  Whole and skimmed UHT milk artificially inoculated with MAP were used to manufacture yoghurt, using two different yoghurt starter cultures. Five commercial fermented milk products were inoculated with MAP. Two different MAP strains were studied. The survival of MAP in all products was monitored by culture over a 6‐week storage per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
3
23
0
1
Order By: Relevance
“…These colonies were also positive for MAP- specific IS900 (Figure 5d). MAP spore survival post exposure to 70°C may in fact not be extremely surprising since many studies have shown the presence of MAP as a food contaminant in pasteurized (also treated at 70°C) milk, cheeses and yogurt [40], [41], [42], [43]. It is currently unknown if the MAP found in these dairy products may exist in a spore or spore-like state.…”
Section: Resultsmentioning
confidence: 99%
“…These colonies were also positive for MAP- specific IS900 (Figure 5d). MAP spore survival post exposure to 70°C may in fact not be extremely surprising since many studies have shown the presence of MAP as a food contaminant in pasteurized (also treated at 70°C) milk, cheeses and yogurt [40], [41], [42], [43]. It is currently unknown if the MAP found in these dairy products may exist in a spore or spore-like state.…”
Section: Resultsmentioning
confidence: 99%
“…If indeed MAP is present in pasteurized milk, it might be transferred to humans upon consumption of by-products. Therefore, it is interesting to gain insights into the behavior of MAP in such products as the acidic nature of yogurt (pH about 4–4.5) generally contributes to the inactivation of bacterial pathogens [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In all samples, MAP counts were low due to the aggressive step of decontamination. van Brandt et al [18] found that initial MAP counts remain unchanged over the 6 weeks of refrigerated storage, regardless of starter culture used and the fat content of milk, but did not evaluate its isolation during preparation. Sung and Collins [29] found that at low pH levels in vitro , MAP expressed two proteins related at the acid tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because M. paratuberculosis is a worldwide problem in cattle and a suspected agent for human Crohn's disease (Hermon-Taylor and Bull, 2002; Divangahi et al, 2008), alternative treatment options are needed to control Johne's disease in dairy herds. Recently, various strains of lactic acid bacteria (LAB), have been shown to inhibit the growth of M. paratuberculosis in fermented food (Van Brandt et al, 2011), providing the potential for its use to control infection in a suitable host. Current animal models for Johne's disease pathogenesis and vaccine studies are either inefficient (e.g., the intraperitoneal infection of mice) or expensive (e.g., the cow or goat models) (Hines et al, 2007).…”
Section: Introductionmentioning
confidence: 99%